Delayed Diagnosis of Pediatric Sternoclavicular Joint Infections and Clavicular Osteomyelitis During the COVID-19 Pandemic: A Report of 3 Cases. (27th September 2022) - Benson, Elizabeth M.; Kothari, Ezan A.; Torrez, Timothy W.; Conklin, Michael J.; Berger, Stephanie; Williams, Kevin A.
Abstract : Sternoclavicular joint infections and osteomyelitis of the clavicle are extremely rare infections, especially in the pediatric population. Early signs of these infections are nonspecific and can be mistaken for common upper respiratory infections such as COVID-19 and influenza. Rapid diagnosis and treatment are critical for preventing potentially fatal complications such as mediastinitis. We present three cases of sternoclavicular joint infections in the past year during the COVID-19 pandemic. All three patients had delayed diagnoses likely secondary to COVID-19 workup. Each patient underwent surgical irrigation and débridement. Two of three patients required multiple surgeries and prolonged antibiotic courses. Placement of antibiotic-impregnated calcium sulfate beads into the surgical site cleared the infection in all cases where they were used. All three patients made a full recovery; however, the severity of their situations should not be overlooked. Children presenting to the hospital with chest pain, fever, and shortness of breath should not simply be discharged based on a negative COVID-19 test or other viral assays. A higher index of suspicion for bacterial infections such as clavicular osteomyelitis is important. Close attention must be placed on the physical examination to locate potential areas of concentrated pain, erythema, or swelling to prompt advanced imaging if necessary.